2020
DOI: 10.1002/adem.201900871
|View full text |Cite
|
Sign up to set email alerts
|

Angle‐Dependent Transitions Between Structural Bistability and Multistability

Abstract: Mechanical metamaterials with multi‐nonpositive indexes, especially for a negative Poisson's ratio (NPR)/zero Poisson's ratio (ZPR), negative stiffness (NS)/zero stiffness (ZS), and negative thermal expansion (NTE)/zero thermal expansion (ZTE), have garnered significant interest due to their unprecedented mechanical properties and functional applications for advanced materials and devices. Architected materials with one abnormal index, such as auxetic materials, have been widely studied based on mature and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 87 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Recent work has demonstrated that the bistability can be extended to multiple states [284]. Such materials have also been fabricated via FDM.…”
Section: Approaches For Bistable Metamaterialsmentioning
confidence: 99%
“…Recent work has demonstrated that the bistability can be extended to multiple states [284]. Such materials have also been fabricated via FDM.…”
Section: Approaches For Bistable Metamaterialsmentioning
confidence: 99%
“…Leveraging mechanical design, the 3D building blocks can be cascaded to create multistable mechanisms with richer potential energy landscapes. [74,75] These mechanisms, in turn, can communicate information by guiding acoustic or electromagnetic waves. [74,[76][77][78][79][80] It has been envisioned that conformable monolithic systems that undergo complex motion directly programmed within the architecture of the material will realize soft robots capable of transforming a simple input, such as a pressure impulse, into a complex sequence of flexion, tension, and torsion outputs.…”
Section: Structural and Microfluidic Logic Elementsmentioning
confidence: 99%
“…Properly designed mechanical metamaterials can show unusual mechanical properties such as negative Poisson's ratio, negative stiffness, energy trapping, etc. [54][55][56][57][58][59][60]. For example, constrained tilted elastic beams can be used to construct multistable mechanical metamaterials (Figure 7a-f).…”
Section: Mechanical Metamaterialsmentioning
confidence: 99%